Study on identification of modal parameters of turbomachinery blade and impeller - Yasutomo KANEKO; Kazushi MORI; Tatsuya FURUKAWA (Nihon Kikai Gakkai ronbunshu, 2020)
To develop turbomachinery blades with high reliability, it is indispensable to verify the natural frequency, the damping, the resonant stress, etc. under operating condition, and utilize these data in the mechanical design of a new blade. BTT (Blade Tip Timing) and the telemetry system have been widely used to measure the modal parameters of turbomachinery blades. In measurement of the modal parameters of blades in rotation, it is well known that the mistuning phenomena make the identification of modal parameters difficult. Namely, because, in a mistuned bladed disk, responses of many vibration modes are superimposed, it becomes difficult to correctly identify the natural frequency and the damping of each vibration mode. This is one of the critical issues to be overcome for developing blades with high reliability. Recently LSCF（Least-Squares Complex Frequency-Domain）method has been proposed as an effective method for identifying the modal parameters from complicated frequency responses. This method was also applied to derive the modal parameters of a bladed disk from the frequency responses expressed by travelling wave coordinates. In this paper, the validity of the LSCF method is verified by numerical simulations, where the modal parameters of mistuned bladed disks are identified from the frequency responses consisting of many vibration modes. In addition, the accuracy of the conventional half power method used in identifying the blade damping is researched.